Utilizing Digital Marketing in The Promotion of Slumpring Go International Tourism in The Industrial Era 4.0: The popularity of Slumpring Market, Cempaka Village, Tegal Regency has made Pancasakti Tegal University lecturers interested in working on tourism potential as a form of community service. - Informatika, Hasbi Firmansyah, M.Kom; BUDIRAHARJO, M.KOM, EKO; Agus, Agus Wibowo; Yoga, Yoga Prihatin; Ria, Ria Indah Fitria (ASEAN Journal of Empowering Community, 2023)
The popularity of Slumpring Market, Cempaka Village, Tegal Regency has made Pancasakti Tegal University lecturers interested in working on tourism potential as a form of community service. The theme of this community service program is International Tourism and The Digital Transformation of tourism and Digital Transformation in Slumpring Tourism, Tegal Regency. Digital marketing in promoting online can use website and mobile media. In industry 4.0, it is an automatic trend for carrying out activities in the business sector. The use of digital marketing in the industrial era 4.0 in the world of tourism is very influential, supported by 5 digital marketing applications, namely websites, online advertising, social media, web forums and mobile applications. By implementing digital marketing tourism will growprofessional, global and international. Information technology is one of the means used to promote tourism from various social media with various digital marketing. With digital marketing, people's interest in going on holiday is increasing. Society in the 4.0 era has been presented with various conveniences from various existing technologies, including the ease of obtaining convenience in tourism. Industry 4.0 in the tourism sector further enhances International Tourism and The Digital Transformation of tourism.